Negative electrode for lithium secondary battery and method for producing same
By forming a multi-layer structure in the negative electrode electrode, optimizing the alignment and porosity of the carbon active material, and applying a magnetic field for orientation, the problems of insufficient wettability and energy density of the natural graphite negative electrode electrode are solved, and efficient electrolyte flow and high energy density are achieved.
Patent Information
- Application Number
- JP2024549545
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-11-25
- Filing Date
- 2023-10-25
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-10-25
AI Technical Summary
When natural graphite is used in the existing negative electrode electrolyte for lithium secondary batteries, the electrolyte decomposition reaction causes expansion, which reduces the electrolyte wetting ability and charge and discharge efficiency.
By forming a multi-layer structure in the negative electrode electrode, the alignment and porosity of the carbon active material of the first and second layers are optimized, and the porosity of the second layer is between 15% and 25%. A magnetic field is used to orient the carbon active material to form an efficient electrolyte flow path.
The negative electrode electrode has achieved high humidity and high energy density on the electrolyte, which improves the charging and discharging efficiency and battery life.
Smart Images

Figure 0007648300000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0160838 dated November 25, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a negative electrode for a lithium secondary battery and a method for producing the same. [Background technology]
[0003] 2. Description of the Related Art In recent years, secondary batteries have been widely used not only in small devices such as portable electronic devices, but also in medium- to large-sized devices such as battery packs for hybrid and electric vehicles and power storage devices.
[0004] Such secondary batteries are power generating elements capable of being charged and discharged and have a laminated structure of a positive electrode / separator / negative electrode. In general, the positive electrode contains a lithium metal oxide as a positive electrode active material, and the negative electrode contains a carbon-based active material such as graphite. During charging, lithium ions released from the positive electrode are absorbed into the carbon-based active material of the negative electrode, and during discharging, the lithium ions contained in the carbon-based active material are absorbed into the lithium metal oxide of the positive electrode, thereby allowing repeated charging and discharging.
[0005] On the other hand, in the negative electrode, amorphous carbon or crystalline carbon is used as the negative electrode active material, and among them, crystalline carbon is mainly used because of its high capacity. Examples of such crystalline carbon include natural graphite and artificial graphite.
[0006] Natural graphite has the advantage of being low-cost and high lithium ion storage capacity due to its high degree of graphitization compared to artificial graphite, but natural graphite has an irregular structure, which causes swelling due to electrolyte decomposition reaction at the edges, and the problem of poor wetting ability to electrolyte can occur, resulting in reduced charge / discharge efficiency and capacity. Therefore, there have been attempts to solve these problems through the sphericity of natural graphite and surface coating treatment, but the developed technologies are either not cost-competitive or have only a limited effect on improving electrolyte wettability and are limited in improving electrical properties. Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a negative electrode for a lithium secondary battery which contains a carbon-based active material such as natural graphite and yet has excellent electrolyte wettability and high energy density, and a method for producing the same. [Means for solving the problem]
[0008] To solve the above-mentioned problems, In one embodiment, the present invention comprises: a negative electrode current collector; a first negative electrode active layer provided on at least one surface of the negative electrode current collector and containing a carbon-based active material; and a second negative electrode active layer provided on the first negative electrode active layer and containing a carbon-based active material; The first negative electrode active layer has an alignment degree (OI) of the carbon-based active material represented by the following formula 1: 1st ) is the degree of alignment (OI) of the carbon-based active material in the second negative electrode active layer. 2nd ) is larger than Provided is a negative electrode for a lithium secondary battery, characterized in that the porosity of the second negative electrode active layer is 15% to 25%:
[0009] [Formula 1] OI=I 004 / I 110
[0010] In formula 1, I 004 represents the area of the peak showing the (0,0,4) crystal plane in X-ray diffraction spectroscopy (XRD) measurement of the negative electrode active layer, I 110 represents the area of the peak indicating the (1,1,0) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD).
[0011] At this time, the degree of alignment (OI) of the carbon-based active material contained in the second negative electrode active layer 2nd ) can be 0.4 to 0.9.
[0012] In addition, the degree of alignment (OI) of the carbon-based active material contained in the first negative electrode active layer 1st ) is the degree of alignment (OI) of the carbon-based active material contained in the second negative electrode active layer. 2nd ) may have a ratio of 105% to 150%.
[0013] The first and second negative electrode active layers may have a total thickness of 50 μm to 300 μm.
[0014] The second negative electrode active layer has a thickness of 0.20 m. 2 / g~0.62m 2 / g.
[0015] In addition, the negative electrode can satisfy the following formula 2 when evaluating wettability with propylene carbonate:
[0016] [Formula 2] 1≦WT / OI 2nd <= 16
[0017] In formula 2, WT represents the time (unit: seconds) required for propylene carbonate to be impregnated when one drop (2 μl to 5 μl) of propylene carbonate is dropped onto a unit area (1 cm × 1 cm) of the negative electrode. OI 2nd represents the degree of alignment of the carbon-based active material contained in the second negative electrode active layer.
[0018] The carbon-based active material may include one or more of natural graphite and artificial graphite.
[0019] Further, in one embodiment, the present invention provides Applying a first negative electrode slurry including a carbon-based active material onto a negative electrode current collector; applying a second negative electrode slurry including a carbon-based active material on the applied first negative electrode slurry; applying a magnetic field to the first negative electrode slurry and the second negative electrode slurry; and drying the first and second negative electrode slurries to which the magnetic field is applied to form a first and second negative electrode active layer, The first negative electrode active layer thus formed has an alignment degree (OI) of the carbon-based active material represented by the following formula 1: 1st ) is the degree of alignment (OI) of the carbon-based active material in the second negative electrode active layer. 2nd ) is larger than A method for producing a negative electrode for a lithium secondary battery, wherein the porosity of the second negative electrode active layer is 15% to 25%:
[0020] [Formula 1] OI=I 004 / I 110
[0021] In formula 1, I 004 represents the area of the peak showing the (0,0,4) crystal plane in X-ray diffraction spectroscopy (XRD) measurement of the negative electrode active layer, I 110 represents the area of the peak indicating the (1,1,0) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD).
[0022] At this time, in the step of applying the magnetic field, a magnetic field of 2,000 G to 6,000 G may be applied.
[0023] The step of applying the magnetic field may be performed for 5 to 60 seconds.
[0024] In addition, the step of forming the first negative electrode active layer and the second negative electrode active layer may include: drying the first negative electrode slurry and the second negative electrode slurry; and rolling the dried first and second negative electrode slurries. Effect of the Invention
[0025] The negative electrode for a lithium secondary battery according to the present invention has a structure in which a first negative electrode active layer and a second negative electrode active layer are sequentially laminated on a negative electrode current collector, and the degree of alignment (OI) of a carbon-based active material is controlled to be smaller in the second negative electrode active layer than in the first negative electrode active layer. By providing a low ratio of voids in the second negative electrode active layer, a flow path through which an electrolyte can move can be maintained inside the negative electrode active layer even after a rolling process of the negative electrode active layer, thereby providing advantages in that the negative electrode has high wettability to an electrolyte and excellent energy density. [Brief description of the drawings]
[0026] [Figure 1] 1 is a cross-sectional view illustrating a structure of a negative electrode for a lithium secondary battery according to the present invention. [Diagram 2] 1A and 1B are images of a cross section of the negative electrode prepared in Example 2 analyzed by a Fourier transform scanning electron microscope / energy dispersive spectroscope (FT-SEM / EDS), in which (A) is a Fourier transform scanning electron microscope (FT-SEM) analysis image, and (B) is a photograph showing the state of voids contained in the negative electrode active layer by component analysis of carbon elements contained in the negative electrode active layer using an energy dispersive spectroscope (EDS). [Diagram 3] 1A and 1B are images of a cross section of the negative electrode prepared in Comparative Example 3 analyzed by a Fourier transform scanning electron microscope / energy dispersive spectroscope (FT-SEM / EDS), in which (A) is a Fourier transform scanning electron microscope (FT-SEM) analysis image, and (B) is a photograph showing the state of voids contained in the negative electrode active layer by component analysis of carbon elements contained in the negative electrode active layer using an energy dispersive spectroscope (EDS). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Since the present invention can be modified in various ways and can have various embodiments, specific embodiments are described in detail in the detailed description.
[0028] However, this is not intended to limit the invention to the particular embodiments, but it should be understood to include all modifications, equivalents, or alternatives falling within the spirit and scope of the invention.
[0029] In the present invention, terms such as "comprise" and "have" are intended to specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof described in the specification, and may be understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.
[0030] In addition, in the present invention, when a layer, film, region, plate, or other portion is described as being "on" another portion, this includes not only the case where it is "directly on" the other portion, but also the case where there is another portion in between. Conversely, when a layer, film, region, plate, or other portion is described as being "under" the other portion, this includes not only the case where it is "directly under" the other portion, but also the case where there is another portion in between. In addition, in the present application, being "on" can include not only the case where it is located at the top, but also the case where it is located at the bottom.
[0031] In the present invention, "containing as a main component" may mean containing 50% by weight or more (or 50% by volume or more), 60% by weight or more (or 60% by volume or more), 70% by weight or more (or 70% by volume or more), 80% by weight or more (or 80% by volume or more), 90% by weight or more (or 90% by volume or more), or 95% by weight or more (or 95% by volume or more) of a defined component based on the total weight (or total volume). For example, "containing graphite as a main component as a negative electrode active material" may mean containing 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, or 95% by weight or more of graphite based on the total weight of the negative electrode active material, and in some cases, it may mean that the entire negative electrode active material is made of graphite and contains 100% by weight of graphite.
[0032] In the present invention, "mAh" is a unit of capacity of a lithium secondary battery, and is called "ampere-hour" and means the amount of current per hour. For example, if a battery capacity is "3000mAh", it means that it can be discharged at a current of 3000mA for one hour.
[0033] The present invention will now be described in more detail.
[0034] <Negative electrodes for lithium secondary batteries> In one embodiment, the present invention comprises: a negative electrode current collector; a first negative electrode active layer provided on at least one surface of the negative electrode current collector and containing a carbon-based active material; and a second negative electrode active layer provided on the first negative electrode active layer and containing a carbon-based active material; The first negative electrode active layer has an alignment degree (OI) of the carbon-based active material represented by the following formula 1: 1st ) is the degree of alignment (OI) of the carbon-based active material in the second negative electrode active layer. 2nd ) is larger than Provided is a negative electrode for a lithium secondary battery, characterized in that the porosity of the second negative electrode active layer is 15% to 25%:
[0035] [Formula 1] OI=I 004 / I 110
[0036] In formula 1, I 004 represents the area of the peak showing the (0,0,4) crystal plane in X-ray diffraction spectroscopy (XRD) measurement of the negative electrode active layer, I 110 represents the area of the peak indicating the (1,1,0) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD).
[0037] The negative electrode for a lithium secondary battery according to the present invention includes a negative electrode active layer including a carbon-based active material on at least one surface of a negative electrode current collector. The negative electrode active layer is a layer that realizes the electrical activity of the negative electrode, and is manufactured by applying an electrode slurry including a negative electrode active material that realizes an electrochemical oxidation-reduction reaction during charging and discharging of the battery to both surfaces of the electrode current collector, and then drying and rolling the same. The negative electrode active layer includes a carbon-based active material as a negative electrode active material to realize electrical activity through a reversible oxidation-reduction reaction during charging and discharging of the battery. Specifically, the carbon-based active material means a material mainly composed of carbon atoms, and such a carbon-based active material may include graphite. The graphite may include at least one of natural graphite and artificial graphite, and preferably includes natural graphite or a mixture of natural graphite and artificial graphite.
[0038] The carbon-based active material is preferably a spherical graphite granule formed by the aggregation of a plurality of flake graphite. Examples of flake graphite include natural graphite, artificial graphite, mesophase calcined carbon (bulk mesophase) made from tar and pitch, graphitized cokes (raw coke, green coke, pitch coke, needle coke, petroleum coke, etc.), etc. In particular, a material assembled using a plurality of highly crystalline natural graphite is preferable. In addition, one graphite granule may be formed by the aggregation of 2 to 100 flake graphite particles, preferably 3 to 20 flake graphite particles.
[0039] Such a carbon-based active material, specifically, graphite, may have a spherical particle shape, and the sphericity of the graphite particles may be 0.75 or more, for example, 0.75 to 1.0, 0.75 to 0.95, 0.8 to 0.95, or 0.90 to 0.99. Here, the "sphericity" may mean the ratio of the shortest diameter (minor axis) to the longest diameter (major axis) among any diameters passing through the center of the particle, and when the sphericity is 1, it means that the particle shape is spherical. The sphericity may be measured using a particle shape analyzer. The present invention has the advantages of realizing a shape of the carbon-based active material close to a sphere, thereby realizing high electrical conductivity of the negative electrode active layer, thereby improving the capacity of the battery, and increasing the specific surface area of the negative electrode active material, thereby improving the adhesive force between the negative electrode active layer and the current collector.
[0040] In addition, the carbon-based active material has an average particle size (D 50 ), specifically, the average particle size (D 50 ) can be shown.
[0041] The average particle size of the spherical natural graphite is preferably as small as possible to maximize the degree of disorder in the direction of expansion of each particle so as to prevent the particles from expanding due to the loading of lithium ions. However, if the particle size of the natural graphite is less than 0.5 μm, a large amount of binder is required due to the increase in the number of particles per unit volume, and the sphericity and sphericity yield may be reduced. On the other hand, if the maximum particle size exceeds 10 μm, the expansion becomes intense, and the adhesion between particles and between the particles and the current collector decreases with repeated charging and discharging, and the cycle characteristics may be significantly reduced.
[0042] Meanwhile, the negative electrode active layer may have a structure in which two individual layers are laminated. Specifically, the negative electrode according to the present invention may have a structure in which a first negative electrode active layer is provided on a negative electrode current collector, and a second negative electrode active layer is provided on the first negative electrode active layer. In this case, the first negative electrode active layer and the second negative electrode active layer contain a carbon-based active material, and the carbon-based active materials contained in each layer may be the same or different.
[0043] In addition, the degree of alignment (OI) of the carbon-based active material contained in each of the first and second negative electrode active layers and the internal porosity of the negative electrode active layer may be individually adjusted to satisfy a specific range in order to increase the energy density of the negative electrode and improve wettability to the electrolyte.
[0044] In general, when a process such as rolling is performed to increase the energy density of a negative electrode containing a carbon-based active material, the size and ratio of the voids distributed between the active materials and the pores distributed inside the active material are reduced, so that there is a limit to the decrease in wettability to the electrolyte and lithium ion mobility. However, the negative electrode according to the present invention can have a flow path through which the electrolyte can move in the negative electrode active layer even when the negative electrode active layer is rolled to increase the energy density by reducing the degree of disorder at the molecular level of the carbon-based active material contained in each layer. Here, "reducing the degree of disorder at the molecular level of the carbon-based active material" means that the crystals of the active material constituting the carbon-based active material particles are distributed to have a predetermined directionality, which may be different from the carbon-based active material particles themselves being arranged to have a specific direction inside the negative electrode active layer.
[0045] In this way, the degree of disorder of the carbon-based active material contained in each layer of the negative electrode is reduced, so that the degree of order (OI) of the carbon-based active material and the internal porosity of the negative electrode active layer can be adjusted to satisfy specific ranges.
[0046] Specifically, in the negative electrode according to the present invention, the carbon-based active material contained in the negative electrode active layer may be aligned at a predetermined angle with respect to the negative electrode current collector. Such alignment of the carbon-based active material may reduce the degree of disorder in the negative electrode active layer, form a flow path for electrolyte movement between the carbon-based active materials constituting the negative electrode active layer, and reduce the electrode resistance. In this case, the degree of alignment (or orientation) of the carbon-based active material (e.g., graphite) may be determined by crystal plane analysis of the carbon-based active material contained in the negative electrode active layer.
[0047] As one example, in the negative electrode active layer, the carbon-based active material is aligned in a certain direction with respect to the negative electrode current collector, and when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD), the average degree of alignment of the carbon-based active material represented by the following formula 1 may satisfy 0.4 to 0.9:
[0048] [Formula 1] OI=I 004 / I 110
[0049] In formula 1, I 004 represents the area of the peak showing the (0,0,4) crystal plane in X-ray diffraction spectroscopy (XRD) measurement of the negative electrode active layer, I 110 represents the area of the peak indicating the (1,1,0) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD).
[0050] The above formula 1 can be an index showing the degree to which the crystal structure of the spherical carbon-based active material is aligned in a certain direction, specifically, with respect to the surface of the negative electrode current collector, during X-ray diffraction measurement. More specifically, the negative electrode active layer shows 2θ=26.5±0.2°, 42.4±0.2°, 43.4±0.2°, 44.6±0.2°, 54.7±0.2°, and 77.5±0.2°, which are peaks for the carbon-based active material graphite during X-ray diffraction measurement. These represent the (0,0,2) plane, (1,0,0) plane, (1,0,1)R plane, (1,0,1)H plane, (0,0,4) plane, and (1,1,0) plane. In addition, the peak appearing at 2θ=43.4±0.2° may be due to an overlap of the (1,0,1)R plane of the carbon-based active material and the peak corresponding to the (1,1,1) plane of the current collector, for example, copper (Cu).
[0051] Among these, the degree of alignment (OI) of the carbon-based active material can be measured by the area ratio of the peak at 2θ=77.5±0.2° indicating the (1,1,0) plane and the peak at 2θ=54.7±0.2° indicating the (0,0,4) plane, specifically, the area ratio obtained by integrating the intensities of the above peaks. Here, the peak at 2θ=54.7±0.2° is a peak indicating the (0,0,4) plane, which is one of the crystal planes of graphite and has a tilt with respect to the negative electrode current collector, so the degree of alignment (OI) closer to 0 means that the tilt with respect to the surface of the negative electrode current collector is closer to 90°, and the larger the value, the closer the tilt with respect to the surface of the negative electrode current collector is to 0° or 180°. In this aspect, in the negative electrode active layer according to the present invention, the carbon-based active material is aligned nearly perpendicular to the negative electrode current collector, for example, at an angle of 60° or more, 70° or more, 70 to 90°, 80 to 90°, 65 to 85°, or 70 to 85° to the negative electrode current collector, and therefore the degree of alignment (OI) of the carbon-based active material may be lower than when the carbon-based active material is not aligned perpendicularly.
[0052] In addition, in the negative electrode of the present invention, the carbon-based active materials contained in the first negative electrode active layer and the second negative electrode active layer may be aligned to have a certain direction with respect to the negative electrode current collector, and thus the carbon-based active materials contained in the first negative electrode active layer and the second negative electrode active layer may have different degrees of alignment (OI). Specifically, the carbon-based active material contained in the first negative electrode active layer may have a higher degree of alignment (OI) than the carbon-based active material contained in the second negative electrode active layer.
[0053] As an example, the degree of alignment (OI) of the carbon-based active material contained in the first negative electrode active layer 1st ) is the degree of alignment (OI) of the carbon-based active material contained in the second negative electrode active layer. 2nd ), and more specifically, may be 110% to 140%, or 110% to 130% greater.
[0054] In this case, the degree of alignment (OI) of the carbon-based active material contained in the second negative electrode active layer 2nd) may be 0.4 to 0.9, and more specifically may be 0.5 to 0.8, 0.6 to 0.8, 0.4 to 0.7, 0.4 to 0.6, or 0.70 to 0.85.
[0055] The negative electrode according to the present invention can reduce the degree of disorder of the carbon-based active material contained in each negative electrode active layer by controlling the degree of order (OI) of the carbon-based active material contained in each negative electrode active layer as described above. As a result, the negative electrode can have a flow path through which the electrolyte can move inside the negative electrode active layer even after the rolling process, so that the negative electrode can exhibit high wettability to the electrolyte even if it has a low proportion of voids inside.
[0056] As an example, the negative electrode according to the present invention can satisfy the following formula 2 when one drop (2 μl to 5 μl) of propylene carbonate (PC), which is a main component of the electrolyte, is dropped onto the second negative electrode active layer located at the outermost side of the negative electrode active layer in order to evaluate the electrolyte wettability of the negative electrode active layer:
[0057] [Formula 2] 1≦WT / OI 2nd <= 16
[0058] In formula 2, WT represents the time (unit: seconds) required for propylene carbonate to be impregnated when one drop (2 μl to 5 μl) of propylene carbonate is dropped onto a unit area (1 cm × 1 cm) of the negative electrode. OI 2nd represents the degree of alignment of the carbon-based active material contained in the second negative electrode active layer.
[0059] Specifically, the negative electrode according to the present invention has a structure in which the above formula 2 is 1 to 16 (i.e., 1≦WT / OI 2nd ≦16), more specifically, 3.5 to 16 (i.e., 3.5≦WT / OI 2nd ≦16), 7.5-15 (i.e., 7.5≦WT / OI 2nd ≦15), 4-12 (i.e., 4≦WT / OI 2nd ≦12), 5-10 (i.e., 5≦WT / OI2nd ≦10), 5-9 (i.e., 5≦WT / OI 2nd ≦9), 9-12 (i.e., 9≦WT / OI 2nd ≦12), 11-15.5 (i.e., 11≦WT / OI 2nd ≦15.5), or 9.5 to 15.5 (i.e., 9.5≦WT / OI 2nd ≦15.5).
[0060] The above formula 2 is a parameter that indicates the correlation between the degree of disorder of the carbon-based active material contained in the second negative electrode active layer and the electrolyte wettability of the second negative electrode active layer. The above formula 2 is expressed by the degree of order (OI) of the carbon-based active material. 2nd ) and the impregnation time of propylene carbonate (PC), which is a main component of the electrolyte. By satisfying Equation 2 within the above range, the negative electrode of the present invention can maintain a flow path for the movement of the electrolyte inside even after rolling of the negative electrode active layer, so that the electrolyte wettability of the negative electrode active layer can be improved and at the same time, the energy density can be further improved.
[0061] Furthermore, the negative electrode according to the present invention may have a low ratio of voids formed in the negative electrode active layer. The voids contained in the inside and outside of the negative electrode active layer may be impregnated with an electrolyte to provide a path for lithium ions to move during charging and discharging of the battery, but if the ratio is excessive, the energy density of the battery may be reduced. Thus, the negative electrode according to the present invention may realize a low porosity by rolling the negative electrode active layer with a low degree of disorder, thereby further increasing the energy density of the negative electrode.
[0062] In this case, the negative electrode active layer, particularly the second negative electrode active layer, may have a porosity of 10% to 30%, specifically 15% to 25%, 18% to 25%, 20% to 25%, or 21% to 24%.
[0063] In this case, the second negative electrode active layer is 0.62 m 2 / g or less, specifically, a BET specific surface area of 0.615 m 2 / g or less, 0.6m 2 / g or less, 0.5m 2 / g or less, 0.20m2 / g~0.62m 2 / g, 0.30m 2 / g~0.62m 2 / g, 0.40m 2 / g~0.62m 2 / g, 0.40m 2 / g~0.60m 2 / g, 0.40m 2 / g~0.55m 2 / g, 0.40m 2 / g~0.50m 2 / g, or 0.58m 2 / g~0.62m 2 The BET specific surface area of the powder can be expressed as 1 / g. Here, the specific surface area can be measured by the BET (Brunauer-Emmett-Teller; BET) method. For example, it can be measured by the BET 6-point method using a porosimetry analyzer (Belsorp-II mini, Bell Japan Inc.) by nitrogen gas adsorption and flow method.
[0064] In the present invention, the porosity and / or BET specific surface area of the second negative electrode active layer, which is located at the outermost position among the negative electrode active layers and is in direct contact with the electrolyte, is adjusted within the above range, thereby making it possible to further increase the energy density of the negative electrode without decreasing the electrolyte wettability of the negative electrode active layer.
[0065] Meanwhile, the average thickness of the negative electrode active layer may be 50 μm to 300 μm, specifically 50 μm to 250 μm, 100 μm to 250 μm, or 100 μm to 200 μm. By adjusting the average thickness of the negative electrode active layer within the above range, the present invention can not only increase the energy density of the electrode, but also uniformly control the degree of disorder of the carbon-based active material contained in the negative electrode active layer.
[0066] In addition, the negative electrode active layer according to the present invention may further selectively contain, in addition to the negative electrode active material as the main component, a conductive material, a binder, other additives, and the like, as necessary.
[0067] The conductive material may include one or more of carbon black, acetylene black, ketjen black, carbon nanotubes, carbon fibers, and the like, but is not limited thereto.
[0068] For example, the negative electrode active layer may contain carbon black, carbon nanotubes, carbon fibers, etc., alone or in combination, as a conductive material.
[0069] At this time, the content of the conductive material may be 0.1 parts by weight to 10 parts by weight, specifically 0.1 parts by weight to 8 parts by weight, 0.1 parts by weight to 5 parts by weight, 0.1 parts by weight to 3 parts by weight, 2 parts by weight to 6 parts by weight, or 0.5 parts by weight to 2 parts by weight. By controlling the content of the conductive material within the above range, the present invention can prevent the resistance of the negative electrode from increasing due to a low content of the conductive material, resulting in a decrease in the charging capacity. In addition, the problem of the content of the negative electrode active material decreasing due to an excessive amount of the conductive material, resulting in a decrease in the charging capacity, or the problem of the rapid charging characteristics decreasing due to an increase in the loading amount of the negative electrode active layer can be prevented.
[0070] The binder is a component that aids in bonding between the active material and the conductive material and between the active material and the current collector, and may be suitably used within a range that does not deteriorate the electrical properties of the electrode. Specifically, the binder may include any one or more selected from the group consisting of vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, and fluororubber.
[0071] The content of the binder may be 0.1 to 10 parts by weight, specifically 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 2 to 6 parts by weight, based on 100 parts by weight of the total negative electrode active layer. By controlling the content of the binder contained in the negative electrode active layer within the above range, the present invention can prevent a decrease in adhesive strength of the active layer due to a low content of the binder, or a decrease in electrical properties of the electrode due to an excessive amount of the binder.
[0072] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, nickel, titanium, calcined carbon, etc., and in the case of copper or stainless steel, it may be surface-treated with carbon, nickel, titanium, silver, etc. The average thickness of the negative electrode current collector may be suitably 1 μm to 500 μm, taking into consideration the conductivity and total thickness of the negative electrode to be manufactured.
[0073] <Lithium secondary battery> In one embodiment, the present invention further comprises: There is provided a lithium secondary battery comprising an electrode assembly including a positive electrode, the negative electrode of the present invention described above, and a separator disposed between the positive electrode and the negative electrode.
[0074] The lithium secondary battery according to the present invention includes an electrode assembly in which a plurality of positive electrodes, a separator, and a negative electrode are sequentially arranged, and an electrolyte composition in which a lithium salt and an electrolyte additive are dissolved in a non-aqueous organic solvent. The lithium secondary battery includes the negative electrode of the present invention, which has a structure in which a first negative electrode active layer and a second negative electrode active layer are sequentially stacked on a negative electrode current collector, and in which the degree of alignment (OI) of the carbon-based active material contained in the second negative electrode active layer is lower than the degree of alignment of the carbon-based active material contained in the first negative electrode active layer, and the porosity of the second negative electrode active layer is low. As a result, the lithium secondary battery has the advantages of being excellent in electrolyte wettability and being able to realize high energy density.
[0075] In this case, the negative electrode has the same configuration as that described above, and therefore a detailed description thereof will be omitted.
[0076] The positive electrode includes a positive electrode active layer prepared by applying a slurry containing a positive electrode active material onto a positive electrode current collector, followed by drying and pressing, and may further include a conductive material, a binder, other additives, and the like as necessary.
[0077] The positive electrode active material is a material capable of electrochemically reacting on the positive electrode current collector, and may include one or more of the lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2 capable of reversibly intercalating and deintercalating lithium ions:
[0078] [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O 2
[0079] [Chemical formula 2] LiM 2 p Mn q P r O 4
[0080] In the above Chemical Formula 1 and Chemical Formula 2, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, and v are 1.0≦x≦1.30, 0.5≦y<1, 0 <z≦0.3、0<w≦0.3、0≦v≦0.1であり、かつy+z+w+v=1であり、 M 2 is Ni, Co or Fe, p is 0.05≦p≦1.0, q is 1-p or 2-p; r is 0 or 1.
[0081] The lithium metal oxides represented by Chemical Formula 1 and Chemical Formula 2 above are materials containing high amounts of nickel (Ni) and manganese (Mn), respectively, and when used as a positive electrode active material, have the advantage of being capable of stably supplying high capacity and / or high voltage electricity.
[0082] In this case, the lithium metal oxide represented by the above chemical formula 1 is LiNi 0.8 Co 0.1 Mn 0.1 O 2 , LiNi 0.6 Co 0.2 Mn 0.2 O 2 , LiNi 0.9 Co 0.05 Mn 0.05 O 2 , LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O 2 , LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O 2、 LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O 2 The lithium metal oxide represented by the above chemical formula 2 may include LiNi 0.7 Mn 1.3 O 4 , LiNi 0.5 Mn 1.5 O 4、 LiNi 0.3 Mn 1.7 O 4、 LifePO 4 , Life q Mn 1-q PO 4 etc., which may be used alone or in combination.
[0083] The positive electrode active material may be included in an amount of 85 parts by weight or more, specifically 90 parts by weight or more, 93 parts by weight or more, or 95 parts by weight or more, based on the weight of the positive electrode active layer.
[0084] The positive electrode active layer may further contain a conductive material, a binder, other additives, and the like in addition to the positive electrode active material.
[0085] In this case, the conductive material is used to improve the electrical performance of the positive electrode, and may be any conductive material commonly used in the art. Specifically, the conductive material may include one or more selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, denka black, ketjen black, super P, channel black, furnace black, lamp black, summer black, graphene, and carbon nanotubes.
[0086] The conductive material may be included in an amount of 0.1 to 5 parts by weight based on the weight of each positive electrode active layer, specifically 0.1 to 4 parts by weight, 2 to 4 parts by weight, 1.5 to 5 parts by weight, 1 to 3 parts by weight, 0.1 to 2 parts by weight, or 0.1 to 1 part by weight.
[0087] In addition, the binder plays a role of binding the positive electrode active material, the positive electrode additive, and the conductive material to each other, and may be used without any particular limitation as long as it has such a function. Specifically, the binder may include one or more resins selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethylmethacrylate, and copolymers thereof. As an example, the binder may include polyvinylidene fluoride (PVDF).
[0088] The binder may be included in an amount of 1 to 10 parts by weight, specifically 2 to 8 parts by weight, or 1 to 5 parts by weight, based on the weight of each positive electrode active layer.
[0089] The total thickness of the positive electrode active layer is not particularly limited, but may specifically be 50 μm to 300 μm, more specifically 100 μm to 200 μm, 80 μm to 150 μm, 120 μm to 170 μm, 150 μm to 300 μm, 200 μm to 300 μm, or 150 μm to 190 μm.
[0090] In addition, the positive electrode may use a positive electrode current collector that has high conductivity without inducing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, etc. may be used, and in the case of aluminum or stainless steel, those that have been surface-treated with carbon, nickel, titanium, silver, etc. may also be used. In addition, the average thickness of the current collector may be suitably applied to be 3 μm to 500 μm, taking into consideration the conductivity and total thickness of the positive electrode to be manufactured.
[0091] Meanwhile, the separator interposed between the positive and negative electrodes of each unit cell is an insulating thin film having high ion permeability and mechanical strength, and is not particularly limited as long as it is one commonly used in the art, specifically, one containing at least one polymer selected from polypropylene, polyethylene, and polyethylene-propylene copolymers having chemical resistance and hydrophobicity may be used. The separator may have a porous polymer substrate such as a sheet or nonwoven fabric containing the above-mentioned polymer, and in some cases, may have a composite separator formed by coating organic or inorganic particles on a porous polymer substrate with an organic binder. In addition, the separator may have an average pore diameter of 0.01 μm to 10 μm and an average thickness of 5 μm to 300 μm.
[0092] Meanwhile, the lithium secondary battery according to the present invention is not particularly limited, and may be a secondary battery having a form that may include a stack type, a zigzag type, or a zigzag-stack type electrode assembly. As one example, the lithium secondary battery according to the present invention may be a pouch type secondary battery or a prismatic type secondary battery.
[0093] <Method of manufacturing the negative electrode> In one embodiment, the present invention further comprises: Applying a first negative electrode slurry including a carbon-based active material onto a negative electrode current collector; applying a second negative electrode slurry including a carbon-based active material on the applied first negative electrode slurry; applying a magnetic field to the first negative electrode slurry and the second negative electrode slurry; and drying the first and second negative electrode slurries to which the magnetic field is applied to form a first and second negative electrode active layer, The first negative electrode active layer thus formed has an alignment degree (OI) of the carbon-based active material represented by the following formula 1: 1st ) is the degree of alignment (OI) of the carbon-based active material in the second negative electrode active layer. 2nd ) is larger than The present invention provides a method for producing a negative electrode for a lithium secondary battery, the method being characterized in that the average internal porosity of the first negative electrode active layer and the second negative electrode active layer is 15% to 25%:
[0094] [Formula 1] OI=I 004 / I 110
[0095] In formula 1, I 004 represents the area of the peak showing the (0,0,4) crystal plane in X-ray diffraction spectroscopy (XRD) measurement of the negative electrode active layer, I 110 represents the area of the peak indicating the (1,1,0) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD).
[0096] In the method for manufacturing the negative electrode according to the present invention, a negative electrode slurry containing a carbon-based active material is applied onto a negative electrode current collector, and a magnetic field is applied to the surface of the applied negative electrode slurry, thereby aligning the carbon-based active material in the negative electrode slurry at a predetermined angle with respect to the surface of the negative electrode current collector (or with respect to the conveying direction of the electrode sheet), thereby reducing the degree of disorder of the carbon-based active material. Then, the negative electrode slurry with the reduced degree of disorder of the carbon-based active material is continuously dried to form a negative electrode active layer, thereby manufacturing the negative electrode.
[0097] Here, the step of applying the negative electrode slurry may be performed in two steps, specifically, the step of applying the negative electrode slurry may include a step of applying a first negative electrode slurry including a carbon-based active material onto the negative electrode current collector, and a step of applying a second negative electrode slurry including a carbon-based active material onto the applied first negative electrode slurry.
[0098] In this case, the carbon-based active materials contained in the first negative electrode slurry and the second negative electrode slurry may be the same or different. When the carbon-based active materials are the same, the conductive materials, binders, additives, etc. contained in the negative electrode slurries may be different, or the content ratios of the carbon-based active materials contained in the negative electrode slurries may be different.
[0099] In addition, the steps of applying the first negative electrode slurry and the second negative electrode slurry may be performed in any manner commonly used in the art without any particular limitations.
[0100] In addition, the step of applying a magnetic field to the first and second negative electrode slurries may be a step of reducing the degree of disorder so that the crystal plane of the carbon-based active material contained in each negative electrode slurry has a predetermined angle with respect to the negative electrode current collector. To this end, the step of applying a magnetic field may be applied to the surface of the negative electrode slurries coated in sequence on the negative electrode current collector, i.e., the exposed surface of the second negative electrode slurry, and the first negative electrode slurry located below the second negative electrode slurry may also have a reduced degree of disorder due to the applied magnetic field.
[0101] In this case, the degree of disorder of the carbon-based active material contained in each negative electrode slurry can be adjusted by the strength of the applied magnetic field, the time of exposure to the magnetic field, and the like.
[0102] For example, in the step of applying a magnetic field, a magnetic field of 2,000 G (Gauss) to 6,000 G (Gauss) may be applied, specifically, a magnetic field of 2,500 G to 5,500 G, 3,000 G to 5,500 G, 3,500 G to 5,500 G, 4,000 G to 5,500 G, 3,500 G to 4,500 G, or 4,500 G to 5,000 G may be applied.
[0103] Furthermore, the step of applying the magnetic field may be performed for 5 to 60 seconds, specifically for 10 to 60 seconds, 10 to 30 seconds, 30 to 60 seconds, 40 to 50 seconds, 15 to 35 seconds, or 10 to 50 seconds.
[0104] As one example, in the step of applying a magnetic field, a magnetic field of 4,700±100 G may be applied to the negative electrode slurry for 12 to 33 seconds.
[0105] In the present invention, by applying a magnetic field to the second negative electrode slurry with the magnetic field strength and application time as described above in the step of applying a magnetic field, it is possible to simultaneously reduce the degree of disorder of the carbon-based active material of the second negative electrode slurry as well as the first negative electrode slurry located below the second negative electrode slurry.
[0106] In addition, forming the first and second negative electrode active layers may include drying the first and second negative electrode slurries and rolling the dried first and second negative electrode slurries.
[0107] At this time, the step of drying the first and second negative electrode slurries may be performed in any manner that can maintain the alignment of the carbon-based active material contained in the negative electrode active layer, without any particular limitations.
[0108] For example, the drying step may be performed by applying thermal energy to the negative electrode slurry using a hot air dryer, a vacuum oven, or the like to dry the negative electrode slurry.
[0109] In addition, the rolling of the dried negative electrode slurry is a step of increasing the density of the negative electrode active layer by applying pressure to the dried negative electrode slurry using a roll press, etc. Here, the rolling may be performed at a temperature condition higher than room temperature.
[0110] Specifically, rolling can be carried out at a temperature of 50°C to 100°C, more specifically, at a temperature of 60°C to 100°C, 75°C to 100°C, 85°C to 100°C, 50°C to 90°C, 60°C to 80°C, or 65°C to 90°C. Specifically, the rolling may be performed at a rolling speed of 2 m / s to 7 m / s, more specifically, at a rolling speed of 2 m / s to 6.5 m / s, 2 m / s to 6 m / s, 2 m / s to 5.5 m / s, 2 m / s to 5 m / s, 2 m / s to 4.5 m / s, 2 m / s to 4 m / s, 2.5 m / s to 4 m / s, 2.5 m / s to 3.5 m / s, 3.5 m / s to 5 m / s, 5 m / s to 7 m / s, 5.5 m / s to 6.5 m / s, or 6 m / s to 7 m / s. The rolling may be carried out under a pressure condition of 50 MPa to 200 MPa, specifically, under a pressure condition of 50 MPa to 150 MPa, 50 MPa to 100 MPa, 100 MPa to 200 MPa, 150 MPa to 200 MPa, or 80 MPa to 140 MPa.
[0111] The present invention can increase the energy density of the negative electrode while minimizing the change in the alignment degree of the carbon-based active material contained in the first negative electrode active layer and the second negative electrode active layer formed by rolling the dried negative electrode slurry under the above-mentioned temperature, speed and / or pressure conditions.
[0112] Meanwhile, the carbon-based active material contained in the negative electrode slurry may include those that are commonly used as carbon-based active materials for lithium secondary batteries. Specifically, the carbon-based active material means a material mainly composed of carbon atoms, and such a carbon-based active material may include graphite. The graphite may include at least one of natural graphite and artificial graphite, and preferably includes natural graphite or a mixture of natural graphite and artificial graphite.
[0113] In addition, the negative electrode slurry may further include a conductive material, a binder, a thickener, and the like in addition to the carbon-based active material, and these may be materials commonly used in the art.
[0114] The present invention will now be described in more detail with reference to examples and experimental examples.
[0115] However, the following examples and experimental examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples and experimental examples.
[0116] <Examples 1 to 3 and Comparative Examples 1 to 2. Production of negative electrodes for lithium secondary batteries> A negative electrode for a lithium secondary battery was manufactured according to the conditions shown in Table 1 below.
[0117] First, natural graphite and artificial graphite were prepared as carbon-based active materials (average particle size: 4±1 μm, sphericity: 0.94±0.2), and a first negative electrode slurry and a second negative electrode slurry were produced using the prepared carbon-based active materials.
[0118] Specifically, for the first negative electrode slurry, mixed graphite, which is a mixture of natural graphite and artificial graphite in a weight ratio of 2:8, was prepared as the negative electrode active material, carbon black was prepared as the conductive material, and carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) were prepared as the binder. 95 parts by weight of mixed graphite, 1 part by weight of carbon black, 1.5 parts by weight of carboxymethyl cellulose (CMC), and 2.5 parts by weight of styrene butadiene rubber (SBR) were mixed with water to a solid content of 50% to produce the first negative electrode slurry.
[0119] The second negative electrode slurry was prepared in the same manner as the first negative electrode slurry, and only artificial graphite was used as the carbon-based active material.
[0120] After each negative electrode slurry was prepared, the first negative electrode slurry and the second negative electrode slurry were cast in order using a die coater onto a copper thin plate (thickness: 8 μm) being transported roll-to-roll (transport speed: 5 m / min). At this time, the first negative electrode slurry and the second negative electrode slurry were cast so that the average thickness was 125 ± 5 μm, respectively, along the transport direction of the copper thin plate.
[0121] A magnetic field of 4,700±100 G was then applied to the surface of the applied second negative electrode slurry as shown in Table 1 below, and the negative electrode slurry to which the magnetic field was applied was dried with hot air to form a negative electrode active layer. The formed negative electrode active layer was rolled at 50±1° C., a transfer speed of 3 m / s, and a pressure shown in Table 1 to manufacture a negative electrode for a lithium secondary battery.
[0122] X-ray diffraction spectroscopy (XRD) was performed on the first and second negative electrode active layers of the manufactured negative electrode to measure the spectra. In the case of the first negative electrode active layer, after measuring the X-ray diffraction spectroscopy (XRD) of the second negative electrode active layer, the second negative electrode active layer was peeled off and removed, and then X-ray diffraction was measured on the exposed surface of the first negative electrode active layer. The measurement conditions for X-ray diffraction (XRD) were as follows:
[0123] - Target: Cu (Kα line) graphite monochromator -Slit: Divergence slit = 1 degree, Receiving slit = 0.1mm, Scattering slit = 1 degree -Measurement area: (1,1,0) plane: 76.5 degrees < 2θ < 78.5 degrees / (0,0,4) plane: 53.5 degrees < 2θ < 56.0 degrees.
[0124] From the spectra measured under the above conditions, the average degree of alignment (OI) of each carbon-based active material represented by Formula 1 was calculated. The results are shown in Table 1.
[0125] [Formula 1] OI=I004 / I 110
[0126] In formula 1, I 004 represents the area of the peak showing the (0,0,4) crystal plane in X-ray diffraction spectroscopy (XRD) measurement of the negative electrode active layer, I 110 represents the area of the peak indicating the (1,1,0) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD).
[0127] In addition, the porosity and BET specific surface area of the second negative electrode active layer were measured using a BELSORP (BET device) manufactured by BEL JAPAN Co., Ltd., and the porosity of the second negative electrode active layer was defined as follows:
[0128] Internal porosity = void volume per unit mass / (specific volume + void volume per unit mass)
[0129] [Table 1]
[0130] In addition, a cross-section of the negative electrode prepared in Example 2 out of the prepared negative electrodes was analyzed using a Fourier transform scanning electron microscope / energy dispersive spectroscopy (FT-SEM / EDS), and the results are shown in Figure 2. The scanning electron microscope analysis was performed at an acceleration voltage of 5.0 kV and a magnification of 700 times, and the results are shown in Figure 2(A). The carbon element contained in the negative electrode active layer was analyzed using an energy dispersive spectroscopy (EDS), and the state of voids contained in the negative electrode active layer is shown in Figure 2(B).
[0131] <Comparative Example 3. Production of negative electrode for lithium secondary battery> A negative electrode for a lithium secondary battery was manufactured in the same manner as in Example 2, except that a magnetic field was not applied after casting the second negative electrode slurry.
[0132] The first and second negative electrode active layers of the prepared negative electrodes had an order of orientation (OI) of the carbon-based active material of 5.41 and 16.87, respectively. The porosity and BET specific surface area of the second negative electrode active layer were 27±1% and 0.626 m, respectively. 2 / g.
[0133] A cross section of the manufactured negative electrode was analyzed using a Fourier transform scanning electron microscope / energy dispersive spectroscopy (FT-SEM / EDS), and the results are shown in Figure 3. The scanning electron microscope analysis was performed at an acceleration voltage of 5.0 kV and a magnification of 700 times, and the results are shown in Figure 3(A). The carbon element contained in the negative electrode active layer was analyzed using an energy dispersive spectroscopy (EDS), and the state of voids contained in the negative electrode active layer is shown in Figure 3(B).
[0134] <Comparative Example 4. Production of negative electrode for lithium secondary battery> A negative electrode for a lithium secondary battery having a single-layered negative electrode active layer was manufactured in the same manner as in Example 2, except that only the second negative electrode slurry was cast onto a copper thin plate (thickness: 8 μm) using a die coater to an average thickness of 250±10 μm.
[0135] The negative electrode active layer of the fabricated negative electrode had an order of order (OI) of 0.79 for the carbon-based active material, and the porosity and BET specific surface area were 23.5±1% and 0.44 m, respectively. 2 / g.
[0136] <Comparative Example 5. Production of negative electrode for lithium secondary battery> A negative electrode for a lithium secondary battery having a single-layered negative electrode active layer was manufactured in the same manner as in Example 2, except that the first negative electrode slurry was cast onto a copper thin plate (thickness: 8 μm) using a die coater to have an average thickness of 125±5 μm, a magnetic field of 6,500±100 G was applied to the surface of the first negative electrode slurry for 15 seconds, and then the second negative electrode slurry was cast onto the first negative electrode slurry to which the magnetic field was applied to have an average thickness of 125±5 μm.
[0137] The first and second negative electrode active layers of the prepared negative electrodes had an order of orientation (OI) of the carbon-based active material of 0.49 and 0.78, respectively. The porosity and BET specific surface area of the second negative electrode active layer were 22.3±1% and 0.415 m, respectively. 2 / g.
[0138] <Examples 4 to 6 and Comparative Examples 6 to 10. Production of Lithium Secondary Batteries> The positive electrode active material is LiNi with a particle size of 5 μm. 0.7 Co 0.1 Mn 0.1 Al 0.1 O 2 The above was prepared, mixed with polyvinylidene fluoride as a carbon-based conductive material and binder in N-methylpyrrolidone (NMP) in a weight ratio of 94:3:3 to form a slurry, which was then cast onto an aluminum sheet, dried in a vacuum oven at 120°C, and rolled to produce a positive electrode.
[0139] A separator made of 18 μm polypropylene was interposed between the obtained positive electrode and the negative electrode produced in each of Examples 1 to 3 and Comparative Examples 1 to 5, and the resulting positive electrode was inserted into a case, and then an electrolyte composition was injected to assemble a lithium secondary battery.
[0140] The type of negative electrode used in each lithium secondary battery is shown in Table 2 below.
[0141] [Table 2]
[0142] <Experimental Example> In order to evaluate the electrolyte wettability and energy density of the negative electrode according to the present invention, the following experiment was carried out.
[0143] a) Evaluation of electrolyte wettability A drop (2 μl to 4 μl) of propylene carbonate (PC) was dropped onto the surface of the second negative electrode active layer of the negative electrodes prepared in Examples 1 to 3 and Comparative Examples 1 to 5, and the time it took for the dropped drop to be completely impregnated into the second negative electrode active layer was measured. At this time, it was determined that the shorter the time it took for propylene carbonate (PC) to be impregnated, the better the electrolyte wettability of the negative electrode active layer was, and the electrolyte wettability parameter of the negative electrode active layer was calculated from the measured value using the following Equation 2. The results are shown in Table 3 below:
[0144] [Formula 2] Wettability parameter = WT / OI 2nd
[0145] In formula 2, WT represents the time (unit: seconds) required for propylene carbonate to be impregnated when one drop (2 μl to 5 μl) of propylene carbonate is dropped onto a unit area (1 cm × 1 cm) of the negative electrode. OI 2nd represents the degree of alignment of the carbon-based active material contained in the second negative electrode active layer.
[0146] b) Energy density evaluation Each of the negative electrodes produced in Examples 1 to 3 and Comparative Examples 1 to 5 was cut into 2 cm 2 A hole was drilled to the size of the negative electrode, and constant current charging and discharging was performed by the three-terminal method to measure the charge and discharge capacity. Specifically, the energy density of each negative electrode was evaluated by fabricating a sample battery including each negative electrode as a sample electrode. At this time, the sample battery was designed to have a structure including a laminate in which each negative electrode, a separator, and a counter electrode were laminated, and a reference electrode was separately introduced on the upper part. In addition, the sample battery was constructed by dissolving LiPF in a mixed solution of ethylene carbonate (EC) and methyl ethyl carbonate (MEC) (EC:MEC=1:2, vol.:vol.) as the electrolyte. 6 A solution in which the above was dissolved to a concentration of 1 M was applied, metallic lithium was used as the counter electrode and the reference electrode, and a polyethylene microporous membrane was used as the separation membrane.
[0147] The resulting sample battery had a current of 0.2 mA / cm for each negative electrode area. 2At a constant current of 0 V (V vs. Li / Li + ) and charge to 0.2mA / cm 2 At a constant current of 1V (V vs. Li / Li + After discharging to 0.1 V, the discharge capacity per unit volume and the initial charge / discharge efficiency per unit volume of each sample battery were measured and calculated. The measured and calculated results are shown in Table 3 below.
[0148] [Table 3]
[0149] As shown in Table 3, the negative electrode for a lithium secondary battery according to the present invention not only has high electrolyte wettability but also has a high energy density. Specifically, the negative electrode prepared in the examples was shown to have a short time of less than 10 seconds to completely absorb propylene carbonate (PC), a main component of the electrolyte (i.e., the time required for impregnation), and was confirmed to have a high initial charge / discharge efficiency of about 94% or more.
[0150] This means that when the negative electrode of the embodiment has a structure in which a first negative electrode active layer and a second negative electrode active layer are sequentially stacked on a negative electrode current collector, and the degree of alignment (OI) of the carbon-based active material contained in the second negative electrode active layer is lower than the degree of alignment of the carbon-based active material contained in the first negative electrode active layer, and the second negative electrode active layer has a low ratio of voids, the negative electrode active layer may include a flow path through which an electrolyte can move even after a rolling process of the negative electrode active layer, thereby realizing excellent energy density while maintaining high electrolyte wettability of the negative electrode active layer.
[0151] These results show that the negative electrode for a lithium secondary battery according to the present invention has excellent electrolyte wettability and a high energy density.
[0152] Although the present invention has been described above with reference to preferred embodiments, it will be understood that a person skilled in the art or having ordinary knowledge in the art may make various modifications and changes to the present invention without departing from the spirit and technical scope of the present invention as described in the claims below.
[0153] Therefore, the technical scope of the present invention is not limited to the contents described in the Summary of the Invention of the specification, but can be defined by the claims. [Explanation of symbols]
[0154] 100: Negative electrode for lithium secondary battery according to the present invention 110: Negative electrode current collector 120:Negative electrode active layer 121: First negative electrode active layer 122: Second negative electrode active layer
Claims
1. a negative electrode current collector; a first negative electrode active layer provided on at least one surface of the negative electrode current collector and containing a carbon-based active material; and a second negative electrode active layer provided on the first negative electrode active layer and containing a carbon-based active material, The second negative electrode active layer has a degree of alignment (O.I 2nd ) of a carbon-based active material represented by the following formula 1 of 0.4 to 0.9: the degree of alignment (O.I 1st ) of the carbon-based active material contained in the first negative electrode active layer is 105% to 150% of the degree of alignment (O.I 2nd ) of the carbon-based active material contained in the second negative electrode active layer; The porosity of the second negative electrode active layer is 15% to 25%. [Formula 1] O.I=I 004 / I 110 In Formula 1, I 004 represents the area of the peak indicating the (0,0,4) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD), I 110 represents the area of the peak indicating the (1,1,0) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD).
2. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the total thickness of the first negative electrode active layer and the second negative electrode active layer is 50 μm to 300 μm.
3. The second negative electrode active layer is 0.20 m 2 / g to 0.62 m 2 2. The negative electrode for a lithium secondary battery according to claim 1, having a BET specific surface area of 100 / g.
4. The negative electrode for a lithium secondary battery according to any one of claims 1 to 3, which satisfies the following formula 2 when evaluating wettability with propylene carbonate: [Formula 2] 1≦WT / O.I 2nd ≦16 In formula 2, WT represents the time (unit: seconds) required for propylene carbonate to be impregnated when one drop (2 μl to 5 μl) of propylene carbonate is dropped onto a unit area (1 cm × 1 cm) of the negative electrode, O.I. 2nd represents the degree of alignment of the carbon-based active material contained in the second negative electrode active layer.
5. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the carbon-based active material comprises at least one of natural graphite and artificial graphite.
6. applying a first negative electrode slurry including a carbon-based active material onto a negative electrode current collector; applying a second negative electrode slurry including a carbon-based active material onto the applied first negative electrode slurry; applying a magnetic field to the first negative electrode slurry and the second negative electrode slurry; and drying the first and second negative electrode slurries to which the magnetic field is applied to form a first and second negative electrode active layer, The second negative electrode active layer has a degree of alignment (O.I 2nd ) of a carbon-based active material represented by the following formula 1 of 0.4 to 0.9: the degree of alignment (O.I 1st ) of the carbon-based active material contained in the first negative electrode active layer is 105% to 150% of the degree of alignment (O.I 2nd ) of the carbon-based active material contained in the second negative electrode active layer; The porosity of the second negative electrode active layer is 15% to 25%. [Formula 1] O.I=I 004 / I 110 In Formula 1, I 004 represents the area of the peak indicating the (0,0,4) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD), I 110 represents the area of the peak indicating the (1,1,0) crystal plane when the negative electrode active layer is measured by X-ray diffraction spectroscopy (XRD).
7. The method for producing a negative electrode for a lithium secondary battery according to claim 6, wherein a magnetic field of 2,000 G to 6,000 G is applied in the step of applying a magnetic field.
8. The method of claim 6, wherein the applying of the magnetic field is performed for 5 to 60 seconds.
9. The step of forming the first negative electrode active layer and the second negative electrode active layer includes: drying the first negative electrode slurry and the second negative electrode slurry; and rolling the dried first and second negative electrode slurries.
Citation Information
Patent Citations
Electrode assembly for rechargeable lithium battery, and rechargeable lithium battery including same
US20220069293A1
Secondary battery, device, artificial graphite, and preparation method therefor
WO2021108983A1
Negative electrode for lithium ion secondary battery
WO2022080836A1